Teknik Supervisi Pendidikan - Nanang Anshori; Meti Fatimah (TSAQOFAH, 2026)
Educational supervision is a strategic effort to improve learning quality and teacher professionalism, thereby requiring a comprehensive understanding of its techniques, implementation, as well as its strengths and weaknesses in the school context. This study aims to examine educational supervision techniques, their implementation in schools, and their contribution to supporting the improvement of educational quality. This study used a qualitative method with a library research approach. Data were obtained from various library sources, such as books and journal articles relevant to educational supervision, and were then analyzed using the Miles and Huberman interactive model, which includes data reduction, data condensation, and conclusion drawing. The results of the study show that educational supervision techniques are divided into two main categories, namely individual techniques and group techniques. Individual techniques include classroom visits, classroom observation, personal conversations, interclass visits, and self-assessment, whereas group techniques include group discussions, workshops, training workshops, and various other collaborative activities. The implementation of supervision is carried out through the stages of planning, implementation, evaluation, and follow-up. Individual techniques have the advantage of providing more specific and in-depth guidance to teachers, whereas group techniques are more efficient and able to encourage collaboration among teachers. The conclusion of this study affirms that selecting and combining appropriate supervision techniques according to teachers’ needs and school conditions is an important factor in improving teacher competence, learning quality, and educational quality in a sustainable manner.